Depression of presynaptic excitation by the activation of vanilloid receptor 1 in the rat spinal dorsal horn revealed by optical imaging - Ikeda Hiroshi; Kusudo Kei; Murase Kazuyuki (SAGE Publishing, 2006)
Abstract In this study, we show that capsaicin (CAP) depresses primary afferent fiber terminal excitability by acting on vanilloid receptor 1 (TRPV1 channels) of primary afferent fibers in adenosine 5'-triphosphate (ATP)- and temperature-dependent manner using two optical imaging methods. First, transverse slices of spinal cord were stained with a voltage-sensitive dye and the net excitation in the spinal dorsal horn was recorded. Prolonged treatment (>20 min) with the TRPV1 channel agonist, CAP, resulted in a long-lasting inhibition of the net excitation evoked by single-pulse stimulation of C fiber-activating strength. A shorter application of CAP inhibited the excitation in a concentration-dependent manner and the inhibition was reversed within several minutes. This inhibition was Ca++-dependent, was antagonized by the TRPV1 channel antagonist, capsazepine (CPZ), and the P2X and P2Y antagonist, suramin, and was facilitated by the P2Y agonist, uridine 5'-triphosphate (UTP). The inhibition of excitation was unaffected by bicuculline and strychnine, antagonists of GABAA and glycine receptors, respectively. Raising the perfusate temperature to 39°C from 27°C inhibited the excitation (-3%/°C). This depressant effect was antagonized by CPZ and suramin, but not by the P2X antagonist, 2', 3'-O-(2,4,6-trinitrophenyl) adenosine 5'-triphosphate (TNP-ATP). Second, in order to record the presynaptic excitation exclusively, we stained the primary afferent fibers anterogradely from the dorsal root. CAP application and a temperature increase from 27°C to 33°C depressed the presynaptic excitation, and CPZ antagonized these effects. Thus, this study showed that presynaptic excitability is modulated by CAP, temperature, and ATP under physiological conditions, and explains the reported central actions of CAP. These results may have clinical importance, especially for the control of pain.